Greetings from Tobago - (:unkn) unknown (H.O. Thomas, [Trinidad and Tobago], 2011)
The postcard shows a scenic view of Rockley Bay in Tobago from Fort King George which was built by the British in 1770s and was used by the army to protect Tobago from their enemies. Postcard number 15036.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Views; Historic sites--Trinidad and Tobago; Bays--Trinidad and Tobago; Fortification--Trinidad and Tobago; Ordnance--Trinidad and Tobago; Fort King George (Tobago)